The Monacan Indian Nation of Virginia : the drums of life - Whitlock, Rosemary (Contemporary American Indian studies., 2008)
Drawing on interviews with 26 Monacans, one Episcopal minister appointed to serve them, one former clerk of the court for Amherst County, and her own story, the author offers accounts of what happened to the Monacan families and how their very existence as Indians was threatened under the Virginia's Racial Integrity Law.